Deepening Democracy in Indonesia? : Direct Elections for Local Leaders (Pilkada) - Sulistiyanto, Priyambudi; Erb, Maribeth (Book collections on Project MUSE., 2009)
Since the fall of long-reigning President Soeharto, in 1998, Indonesia has been in an era of transition, away from an authoritarian regime, and on a "quest for democracy". This quest started with decentralization laws implemented in 2001, which gave greater autonomy to the regions, and continued with the direct elections for the national and local legislatures and the President in 2004. The latest development in this democratization process is the implementation of a system for the direct ele ...